Improvement of Students' Problem-Solving Skill on Physics Learning: A Meta-Analysis - Octa Qamar Rachmawati; Endang Purwaningsih; Parno Parno (Universitas Lambung Mangkurat, 2024)
Problem-solving skills can be realised by not necessarily depending only on how much students' maturity level is, but also on the problems they experience directly. This study looked into how students' problem-solving skills may be improved in physics learning by paying attention to the level of education, models, media, and learning topics used. This study employs a meta-analysis of 14 scientific publications on student problem-solving skills in physics education, with a focus on articles that were published between 2017 and 2022, accepted by Scopus and SINTA, employing quasi-experimental research designs, satisfying the statistical data requirements for calculating effect sizes, and providing details on the subjects, media, learning models, and educational level in physics education. The data analysis approach was executed using the VOSviewer tool for bibliometric analysis and effect size estimates for metadata analysis. According to the meta-analysis results, students' physics learning outcomes would greatly benefit from exercising their problem-solving abilities, with an average effect size of 1.29 and an influence of 88%. Using the Project-Based Learning (PjBL) learning model in high schools, together with student worksheet learning materials on heat energy, would significantly enhance students' problem-solving abilities in physics classes. This meta-analysis study intends to provide teachers with a standard to measure their choices of models, media, and lesson subjects to improve their students' ability to solve problems when studying physics.